The Effectiveness of the Implementation of a Premarital Course as a Requirement for Marriage Registration - Nur Salim; Syamsuddin Syamsuddin; Baehaqi Baehaqi (al-Afkar, Journal For Islamic Studies, 2026)
This study examines the effectiveness of the implementation of the prospective bride and groom course (Kursus Calon Pengantin or Suscatin) as a prerequisite for premarital registration at the Office of Religious Affairs (Kantor Urusan Agama–KUA) in Banyudono District, Boyolali Regency. Premarital education is considered an important preventive effort to improve marital readiness and minimize potential family conflicts and divorce. However, the effectiveness of its implementation at the local level still requires empirical evaluation. This research employed a qualitative field research approach conducted at KUA Banyudono. Data were collected through observation, in-depth interviews with key informants such as the head of KUA, marriage counselors, and prospective brides and grooms, as well as documentation related to the implementation of the premarital course program. The collected data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the prospective bride and groom course at KUA Banyudono has generally been conducted according to government guidelines and provides participants with knowledge regarding marriage procedures, religious values, family law, reproductive health, marital psychology, and family management. The program contributes to improving the understanding and readiness of prospective couples in preparing for married life. However, its implementation has not yet been optimal due to limited training duration, infrequent program scheduling, and budget constraints affecting the overall effectiveness of the program.